1993
DOI: 10.1213/00000539-199307000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Regional Ophthalmic Anesthesia Produced by pH-Adjusted 0.75% and 0.5% Bupivacaine and 1% and 1.5% Etidocaine, All with Hyaluronidase

Abstract: Two concentrations of etidocaine (1 and 1.5%) and of pH-adjusted bupivacaine (0.5 and 0.75%, pH 6.8), all fortified with hyaluronidase, were compared as local anesthetics in regional ophthalmic surgery for cataract extraction. The series comprised 160 patients assigned randomly to four groups (n = 40). Each patient received one of the four anesthetics in a double blind manner. The technique used was an inferolateral intraconal injection (3 mL) followed by a medial extraconal injection (3 mL). Supplemental inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 0 publications
0
34
1
1
Order By: Relevance
“…Thus, equal concentrations of the two local anaesthetics were not used in this study, as good akinesia is mandatory in cataract surgery. Bupivacaine has been shown to provide adequate globe akinesia and sensory analgesia as a 0.75% concentration and consequently has been recommended for regional ophthalmic anaesthesia [10,15]. Epidural studies comparing 0.75% bupivacaine with 1% ropivacaine have shown that bupivacaine provides an equally good sensory block as ropivacaine and a similar or a slightly better motor block [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, equal concentrations of the two local anaesthetics were not used in this study, as good akinesia is mandatory in cataract surgery. Bupivacaine has been shown to provide adequate globe akinesia and sensory analgesia as a 0.75% concentration and consequently has been recommended for regional ophthalmic anaesthesia [10,15]. Epidural studies comparing 0.75% bupivacaine with 1% ropivacaine have shown that bupivacaine provides an equally good sensory block as ropivacaine and a similar or a slightly better motor block [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Eye movements were measured postinjection in millimetres at 5 and 10 min in all four directions of the compass by the same observer using the method described by Kestenbaum [10]. The degree of globe akinesia was categorised using the method described by Sarvela [11] (Table 1). The need for supplementary blockade was at the discretion of the anaesthetist who conducted the original block and, if required, was performed at 10 min with 3.5 ml 2% plain lignocaine using an inferotemporal approach.…”
Section: Methodsmentioning
confidence: 99%
“…After topical anaesthesia with oxybuprocaine, the first inferolateral intraconal injection of 3 ml pH-adjusted bupivacaine 0.75% with hyaluronidase (Table I, mixture #2) was administered through the conjunctiva to all patients with a 31 mm 27-G sharp needle (Visitec Company, FL, U.S.). 9 The patients were in the primary gaze position. Gentle digital massage was applied for one minute after the injection.…”
Section: Methodsmentioning
confidence: 99%